Civil society organizations against terrorism: case studies from Asia - Gunaratna, Rohan; Aslam, Mohd Mizan (Routledge studies in the politics of disorder and instability, 2021)
Introduction (Rohan Gunaratna and Mohd Mizan Aslam) 1. Counter Terrorism in Asia -- The State Partnership with Civil Society Organizations (Rohan Gunaratna) 2. Critical Role of Civil Society Organizations in Combatting Terrorism (Mohd Mizan Aslam) 3. Separatism, Terrorism and Public Safety: A Retrospective Look at the LTTE and Sri Lankan State (Malkanthi Hettiarachchi) 4. Combating Terrorism Through Community Engagement: Experiences From Malaysia And Indonesia (Ummu Atiyah Ahmad Zakuan and Seniwati) 5. Collaborative Governance in Terrorist Rehabilitation Program in Indonesia (Stanislaus Riyanto, Amy YS Rahayu and Benny J. Mamoto) 6. The Case of Malaysia Post General Election 2018: Society-State Partnership in Combatting Terrorism (Dina Zaman) 7. Counter Violent Extremism: A Collaboration Between The University And The Government of Indonesia (Fajar Erikha, Any Rufaedah, Idhamsyah Eka Putra and Vici Sofianna Putera) 8. Islam, State, Security and Peaceful Co-existence in Myanmar (Maulana Akbar Shah U Tun Aung) 9. The Role of Civil Society in Preventing and Countering Violent Extremism in Bangladesh (Iftekharul Bashar)